Prohibited Expression in Wedding Advice: Entextualization of Pasang ri Kajang - Harlinah Sahib (Hasanuddin University, 2019)
This research is entitled Prohibited expression in wedding Advice: Entextualization of Pasang ri Kajang.The objectives of this research is: 1). To disclose denotational text uttered in wedding advice of ethnic Kajang. 2).To reveal interactional text in wedding advice of ethnic Kajang.3). In addition to denotational and interactional text, this research used semiotic mediational approach to relate between denotational and interactional text of wedding advice Qualitative method was used in obtaining the data whereas the researcher herself had a role as a key instrument which has the to master the field being researched and the preparation to come to the object of the research. The data of wedding advice were obtained through, observation, interview, and note taking. Whereas the result of the research shows that denotational text is related to the structure of utterances or text sentences. Interactional text on the other hand is a text based upon social relation which emphazises on social aspect of language. Apart from denotational and interactional text, semiotic mediational approach was used to relate the two texts denotational text and interactional text ( text-context) which is shown by indexical cues.